Constituição social, interferências e contornos: o arquivo pessoal do Monsenhor João Maria Balen e o arquivo histórico Monsenhor Ruben Neis (1887-1978) - Campos, Vanessa Gomes de (2022)
This dissertation aims to analyze the intricate relationship between the personal archive of Monsignor João Maria Balem and the place that holds it, the Monsignor Ruben Neis Historical Archive (AHMRuN) – formerly known as the Historical Archive of the Metropolitan Curia of Porto Alegre. Starting from the outline of the contours and social constitution of the personal archive of Monsignor João Maria Balem (1887-1978), a priest of the Archdiocese of Porto Alegre, which was bequeathed to Monsignor Ruben Neis when he was responsible for the then Historical Archive of the Metropolitan Curia, we find important elements about the constitution of the institutional archive itself. This is a multidisciplinary proposal, in which we use categories from Archival Science alongside the historicity necessary to the subject, reinforcing the interaction between both disciplines. Based on a reflection on ecclesiastical archives, we approach the AHMRuN in order to understand how its constitution occurred as an organ of the archdiocesan structure. After learning about the place where Monsignor's personal archive is held... João Maria Balem, we have come to identify it as an archival category, beyond its configuration, with the accumulating individual, the owner, as the guiding axis. Upon examining the personal archive, we note the important relationship with the Archive that holds it, due to the "intermediate subjectivities" (HEYMANN), that is, the interferences in the accumulation and treatment dispensed by Monsignor Ruben Neis, which allows us to highlight the "layers of interventions" (SCHWARTZ; COOK) in the process. In this sense, we understand that the AHMRuN (Archive of the Historical and Cultural Heritage of the National Historical and Artistic Heritage) is more than a reflection of a project of the Catholic Church (SCHEFFER), since its composition is essentially subsidiary to the actions of agents such as Balem and Neis. Consequently, just as João Maria Balem's personal archive was constituted by particular interests, associated with the worldviews and historical perspectives of the individuals involved, especially Neis. Thinking about the social constitution of archives means reflecting on the role of these agents and, currently, with the professionalization of the field, on methodological transparency, consciously developing work that will give meaning to the materials that will be used as historical sources.